Preliminary Carbon Untilization And Storage Screening Of Oil Fields In South Sumatra Basin - Sugihardjo Sugihardjo; Usman Usman; Edward ML Tobing (Scientific Contributions Oil and Gas, 2012)
Carbon utilization in oil fi elds as EOR project has becomes main issue nowdays. Therefore preliminary CO2-EOR screening has been done for the oil fi elds laid on South Sumatra Basin, where CO2 emission arise from a number different sources of activities in South Sumatra area. Around 103 oil fi elds and consisting 581 reservoirs have been analysis to select which of those fi elds fulfi ll CO2 injection criteria. The criteria applied of the selection are based on EOR Screening Criteria Revisited papers introducing by J.J Taber at. All. 1977. The results of the screening are categorized as miscible, immiscible and failed for CO2 injection. Afterward, CO2 storage and incremental oil recovery due to CO2 injection were calculated using equation normally used in the oil industries. The incremental oil recovery due to CO2-EOR has been assumed as high as 12% of OOIP at miscible process and only 5% for immiscible displacement. The calculation of CO2 storage is based on the ultimate primary recovery for each fi eld in addition of the additional recovery due to CO2-EOR. Both primary and tertiary recovery have been used as the basic of calculating the CO2 storage. The results of the screening whether reservoir categories in immiscible, miscible injection and failed to fulfi ll EOR-CO2 injection criteria can be summarized as follow: 18 fi elds immiscible, 77 miscible, and 7 failed. Total incremental oil recovery estimate from CO2-EOR is approximately 480.5 MMSTB. While the total CO2 storages estimate are about 70 MMton for voidage replacement due to production at ultimate recovery and 22 MMton at EOR-recovery, so the total CO2 storage is approximately 92 MMton.